2013
DOI: 10.1080/13632469.2012.762955
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topology Irregularities and Construction Quality on Life-Cycle Cost of Reinforced Concrete Buildings

Abstract: Life-cycle cost (LCC) analysis entails consideration of building performance throughout the structures' life. The impact and interaction of topology irregularities and construction quality (CQ) onLCC, however, are often ignored and require a more detailed evaluation. In this article, different levels and interaction of soft story (SS) and CQ are analytically modeled to quantify corresponding fragility curves and LCC (by considering hazard level, limit state cost, and probability of being in different damage st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…The figure shows that the number of severe heat stress hours (WBGT ≥ 25) are higher in the case of a lower star-rated houses compared to a higher star-rated houses at a constant meant T. Fig. 9.4 Heat stress hours against mean outdoor temperature (Mean T) in different star rated houses [54] The probabilities of experiencing heat stress by the occupants in different energy star rated houses were calculated using the following formula [57]:…”
Section: Mitigation Of Heat Stress Risk Through Building Energy Retrofittingmentioning
confidence: 99%
“…The figure shows that the number of severe heat stress hours (WBGT ≥ 25) are higher in the case of a lower star-rated houses compared to a higher star-rated houses at a constant meant T. Fig. 9.4 Heat stress hours against mean outdoor temperature (Mean T) in different star rated houses [54] The probabilities of experiencing heat stress by the occupants in different energy star rated houses were calculated using the following formula [57]:…”
Section: Mitigation Of Heat Stress Risk Through Building Energy Retrofittingmentioning
confidence: 99%
“…Based on the concept and procedure of LCC analysis of concrete structures presented in previous sections, four papers are introduced herein, [19], [20], [21], and [22]. The aim of this section is to present applications and case studies written by experts on the advanced technologies for estimating the LCC of structures such as buildings and bridges, considering, in some situations, the risk.…”
Section: Case Studiesmentioning
confidence: 99%
“…The impact and interaction of soft story irregularities and construction quality on LCC of reinforced concrete buildings under seismic hazard are investigated in [21]. Results of the analytical works presented in that reference showed that the impact of construction quality was of paramount importance in the overall LCC assessment.…”
Section: Case Studiesmentioning
confidence: 99%
“…Based on the concept, procedure, and flowchart of LCC analysis of concrete structures presented in previous sections, three papers are introduced herein (Val and Stewart 2003;Tesfamariam et al 2013;Safi et al 2015). To obtain the best balance of the safety, economy and sustainability requirements, LCC estimation of structure and infrastructure must be included in the decision-making process.…”
Section: Case Studymentioning
confidence: 99%
“…Results of the LCC analysis can be applied to select optimal strategies improving durability of RC structures in marine environments. Tesfamariam et al (2013) investigated the impact and interaction of soft story irregularities and construction quality on LCC of RC buildings under seismic hazard. Results of their analytical works showed that the impact of construction quality was of paramount importance in the overall LCC assessment.…”
Section: Case Studymentioning
confidence: 99%